Effects of a Four-Day Mindfulness Intervention on Teachers’ Stress and Affect: A Pilot Study in Eastern China - Song, Xiaolan; Zheng, Ming; Zhao, Huiwen; Yang, Tianqi; Ge, Xingcheng; Li, Hongmei; Lou, Ting (Frontiers in Psychology, 2020)
Stress is becoming increasingly prevalent among teacher groups, and this is problematic for education. Mindfulness training (MT) is a well-supported way to help various populations cope with and reduce stress. In this study, a 4-day intensive MT program that aimed to increase teachers’ emotional health was developed and implemented into the existing post-service education for teachers in eastern China. A total of 161 teachers voluntarily enrolled in the course and were assigned to either the mindfulness group or the waitlist group. Participants completed measures of mindfulness, positive affect, negative affect, and perceived stress before and after the program. The results showed that MT had statistically significant positive effects on mindfulness, negative affect, and stress. The present findings indicate that a 4-day intensive MT program is a promising way to decrease teachers’ stress and improve their emotional health. The practical meaning of the short-term intensive MT program for teachers is discussed. It is easier for teachers to enroll such a short-term training program, as it may have higher acceptance and feasibility than an 8-week training program in some areas. Clinical Trial Registration:www.ClinicalTrials.gov, identifier ChiCTR2000029653.